Simi 2017 2017
DOI: 10.21698/simi.2017.0037
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Fungal and Streptomycete Strains to Trifluralin and Magnetite Nanoparticles

Abstract: The aim of this study was to estimate the sensitivity of microorganisms, isolated from soil long-term polluted with obsolete pesticides, to magnetite (Fe3O4) nanoparticles and fluorinated dinitroaniline herbicide trifluralin, and to evaluate the inhibition activity of these substances. The response of fungi and streptomycete strains to the presence of magnetite nanoparticles in culture media is individual to each microorganism. For the most of studied microorganisms, the addition of trifluralin to culture medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In all cases, the concentration and size of nanoparticles played an important role. In the literature, only one experiment on the direct effects of nZVI on fungi strain of Aspergillus versicolor, except our investigations (Postolachi et al, 2017), has been published (Diao&Yao, 2009). The authors have shown that even when the fungal culture was treated with a relatively high concentration of nZVI, the effect on its viability was zero.…”
Section: Introductionmentioning
confidence: 99%
“…In all cases, the concentration and size of nanoparticles played an important role. In the literature, only one experiment on the direct effects of nZVI on fungi strain of Aspergillus versicolor, except our investigations (Postolachi et al, 2017), has been published (Diao&Yao, 2009). The authors have shown that even when the fungal culture was treated with a relatively high concentration of nZVI, the effect on its viability was zero.…”
Section: Introductionmentioning
confidence: 99%